Ti doped amorphous carbon (Al/Ti-a:C/p-Si/Al) photodiodes for optoelectronic applications - Aslan, Naim; Koc, Mumin Mehmet; Dere, Aysegul; Arif, Bilal; Erkovan, Mustafa; Al-Sehemi, Abdullah G.; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2018)
Electrochemical deposition technique was used to fabricate titanium doped amorphous carbon (Ti doped a:C) Al/Ti-a:C/p-Si/Al photodiode. The effects of illumination on the current voltage (I-V) characteristics of the Al/a:C/p-Si/Al doped Ti diode for optoelectronic applications were investigated. The reverse current of the diode increased with the increasing illumination intensities when the bias voltage was applied. By using the forward bias I-V characteristics, the ideality factor (n) and barrier height (Of)) of Al/Ti-a:C/p-Si photodiode structure was found as 1,84 and 0,50 eV, respectively. In addition, the capacitance voltage (C-V) and conductance voltage (G-V) measurements of the diode were studied in the frequency range of 100 kHz-600 kHz. The measured values of the capacitance decreased with the increasing frequency. The photoelectrical properties of Al/Ti-a:C/p-Si/Al device indicates that the photodiode investigated in this paper has great potential to be used in optoelectronic device applications and in industry. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Ti doped a:C; Current-voltage characteristics; Electrodeposition technique